Lipid Infusions in Man - Hovig, T; Grøttum, K. A (Thrombosis and Haemostasis, 1973)
The soybean lipid emulsion “Intralipid” was infused in 10 volunteer individuals, and platelets, obtained up to 22 hours after the infusions, were studied by transmission and scanning electron microscopy. Using negative staining technique, platelet coating with lipid particles could be demonstrated. Platelet engulf ment of the lipid particles was found in ultrathin sections. The lipid particles appeared to enter the platelets via invaginations of the surface membranes and were located in vacuoles and in’ ‘humps”. The platelet shape and internal structure was strikingly well preserved and no evidence of platelet aggregation was demonstrated. Small platelet cytoplasmic fragments containing lipid were observed, and it is suggested that these may be pinched off from the platelets. Both with negative staining and in scanning electron micrographs occasional clumps of lipid particles were observed, and the possibility can not be excluded that such clumps may interfere with microcirculatory flow.